Use of the Recombinant Tissue Plasminogen Activator in the Management of Complex Infected Intraperitoneal Fluid Collection - Aibek E. Mirrakhimov; Michel Boivin (Case Reports in Infectious Diseases)
Intra-abdominal infections and infected fluid collections are the result of local infection typically involving the gastrointestinal or genitourinary tract. These infections are usually polymicrobial. The management of such patients should include source control and appropriate antimicrobial therapy. Source control is essential and can be achieved either surgically or by percutaneous drainage of intra-abdominal fluid collection. Interventional radiology drainage of intra-abdominal fluid collections may be especially important in patients with high surgical risk or in patients who refuse surgery. Below, we present a case of successful use of recombinant intraperitoneal tissue plasminogen activator use in a patient with a complex polymicrobial fluid collection.